Seasonal variation of diversity, weathering, and inventory of microplastics in coast and harbor sediments - Chen, Chih-Feng; Ju, Yun-Ru; Lim, Yee Cheng; Chen, Chiu-Wen; Dong, Cheng-Di (The Science of the total environment, 2021)
Spatiotemporal variations in the abundance of microplastics (MPs) in surface sediments along the southwestern coast of Taiwan (including harbor and coastal regions) were investigated and the diversity, degree of weathering, and inventory of MPs in the sediments further quantified. The spatiotemporal variations of MP characteristics were used to assess possible transport routes of MPs. Results indicated that the average MP abundance in the partially-enclosed harbor region was 79.3 MPs in 1 kg dry sediment (item/kg dw), which was 3–5 times higher than that in the coastal region. Average MP abundance during the dry season (36.5 ± 52.2 item/kg dw) was relatively higher than that during the wet season (22.3 ± 23.2 item/kg dw). The dominant MPs were small (0.1–1.0 mm, 90%), colored (62.3%), and consisted mainly of fibers (54.1%) and fragments (40.5%). Analysis by μFTIR revealed the presence of ten types of polymers in the MPs, with the most abundant being polypropylene (35.1%), rayon (33.2%), and polystyrene (10.0%). Values of the microplastic diversity integrated index (MPDII) indicated that MP diversity was greater in the harbor region (MPDII = 0.62) than in the coastal region (MPDII = 0.51–0.54), and greater during the wet season (MPDII = 0.60) than during the dry season (MPDII = 0.50). As indicated by values of the MP carbonyl index (CI), the MPs exhibited a high degree of oxidation (CI >0.31) that appeared unrelated to spatiotemporal variations. In the dry season, MP inventory was 12.2 tons and the wet season inventory was 8.1 tons. The hydrodynamic forces may be an influenced force for the spatiotemporal distribution patterns of the MPs in surface sediments. MPs could accumulate in the surface sediments during the dry season and resuspend in the wet season with the higher rainfall and then migrate towards the deep sea following the water flow. [Display omitted] •Spatiotemporal changes of MPs in harbor and coastal sediments were investigated.•Higher MP abundance and inventory and lower MP diversity were found in dry season than in wet season.•No significant difference in the degree of weathering MPs in sediments between dry and wet seasons•MPs in the sediments accumulated during the dry season and were transported during the wet season.•Season's transition may be an influencing factor of MP gradual migration towards the deep sea.